2018
DOI: 10.1177/1940082918764635
|View full text |Cite
|
Sign up to set email alerts
|

Diet Selection of Leopards (Panthera pardus) in a Human-Use Landscape in North-Eastern India

Abstract: There is increasing evidence of large carnivores using human-use areas, but our understanding of their ecology in such landscapes is limited. The role of wild and domestic prey in sustaining populations of carnivores in human-use landscapes could be significant but is currently poorly documented. We studied the prey composition and diet selection of leopards (Panthera pardus) in a forest and tea-garden landscape in northeastern India where the population density is greater than 700 people per km 2 and average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…There is increasing evidence that poor livestock protection practices, sometimes in combination with low wild prey density, lead to livestock depredation by large felids (Athreya et al, 2016;Shehzad et al, 2015;Suryawanshi et al, 2017;Kshettry, Vaidyanathan & Athreya, 2018). Most of the information on livestock depredation by large felids in tropical areas are from in, or around, protected areas (Patterson et al, 2004;Harihar, Pandav & Goyal, 2011;Khorozyan et al, 2015) where livestock are only an alternative prey.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that poor livestock protection practices, sometimes in combination with low wild prey density, lead to livestock depredation by large felids (Athreya et al, 2016;Shehzad et al, 2015;Suryawanshi et al, 2017;Kshettry, Vaidyanathan & Athreya, 2018). Most of the information on livestock depredation by large felids in tropical areas are from in, or around, protected areas (Patterson et al, 2004;Harihar, Pandav & Goyal, 2011;Khorozyan et al, 2015) where livestock are only an alternative prey.…”
Section: Introductionmentioning
confidence: 99%
“…One would expect livestock losses to be very high because of the absence of wild herbivores in this landscape (Kshettry et al, 2018). However, 242 livestock killed in the 179 km 2 intensive study area were reported as killed by leopards over three years despite extremely high densities of livestock (Athreya et al, 2014), and a high density of leopards (Athreya et al, 2013).…”
Section: Compensation Payment For Livestock Lossesmentioning
confidence: 96%
“…There is increasing evidence that poor livestock protection practices, sometimes in combination with low wild prey density, lead to livestock depredation by many individual large felids within a population (Athreya et al, 2014;Shehzad et al, 2014;Suryawanshi et al, 2017;Kshettry, Vaidyanathan & Athreya, 2018). Most of the information on livestock depredation by large felids in tropical areas are from in, or around, protected areas (Patterson et al, 2004;Harihar, Pandav & Goyal, 2011;Khorozyan et al, 2015) where livestock are only an alternative prey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leopards are found in a wide range of habitat types from tropical, subtropical and humid forests, mountain, savannah and scrub through to deserts (Nowell and Jackson 1996;Sanei et al 2011a;Stein and Hayssen 2013;Shehzad et al 2014;Athreya et al 2016). They feed on a broad range of prey species, such as ungulates, birds, rodents and reptiles (Sanei et al 2011b;Mondal et al 2012a;Shehzad et al 2014;Kshettry et al 2018). Leopards are wide-ranging carnivores.…”
Section: Introductionmentioning
confidence: 99%